The effect of the walk-bike on quality of life and exercise capacity in patients with idiopathic pulmonary fibrosis: a feasibility study - Wapenaar, Monique; Bendstrup, Elisabeth; Molina-Molina, Maria; Stessel, Maarten; Huremovic, Jasmina; Bakker, Eric; Kardys, Isabella; Aerts, Joachim; Wijsenbeek, Marlies (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Idiopathic pulmonary fibrosis (IPF) is characterized by progressive loss of pulmonary function and exercise capacity, leading to loss of quality of life and often social isolation. A new walking aid, the walk-bike, showed an improvement in exercise performance in COPD patients. Aims of this pilot study were to evaluate feasibility of a homebased walk-bike intervention study in IPF patients and to explore the effect of the walk-bike on quality of life (QoL) and exercise capacity. Twenty-three patients with IPF were included in a randomized multicenter crossover study with 8 weeks of standard care and 8 weeks of walk-bike use at home. Ten patients completed both study phases. Study barriers included reluctance to participate and external factors (e.g. weather and road conditions) that hampered adherence. Patients’ satisfaction and experience with the walk-bike varied greatly. After training with the walk-bike, health-related QoL (St. George’s Respiratory and King’s Brief Interstitial Lung Disease questionnaires) demonstrated a tendency towards improvement, exercise capacity did not. A clinically important difference was found between 6-minute walk test with the walk-bike and the standard test; median (range) respectively 602 m (358-684) and 486 m (382-510). Conclusions: Due to practical barriers a larger study with the walk-bike in patients with IPF seems not feasible. Individual patients may benefit from the use of a walk-bike as it improved action radius and showed a tendency towards improvement in QoL. No effect on exercise capacity was observed.